3. PENGARUH PERUBAHAN ORIENTASI KEBIJAKAN AMERIKA SERIKAT TERHADAP PERDAGANGAN DAN PRODUKSI NARKOBA DI KOLOMBIA MELALUI PLAN COLOMBIA TAHUN 2000 – 2005 - Sari, Dira Permata; Utomo, Tri Cahyo; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The trade and production of illegal drugs such as Cocaine in Colombia have given directimpact which threatening the security of United States' homeland, it's proved from the factthat 90% of Colombian's cocaine entered U.S domestic market. As country that has beenlong-identified as anti-drugs state, United States were responsible for securing its landfrom the threat of illegal drugs both in domestic and regional scope. Thus, U.S has beenproviding assistance namely Plan Colombia to fight the trade and production of Cocaine inColombia for six years. During the implementation of Plan Colombia, U.S faced thefrightening event of 9/11 which shifted the policy from War on Drugs to War on Terror.This research aimed to analyze the impact of U.S shifted policy toward drug's traffickingand production in Colombia. Identity concept of Constructivist theory of InternationalRelations used as research framework. The research conducted in explanative type usingqualitative data technic through library data collection. The result of this researching wouldshow the impact given from U.S shifted policy towards trade and production of drugs inColombia.